Model Pembelajaran Berbasis Masalah untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pembelajaran IPS - Idha Lusmianingtyas; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
This research was conducted by researchers in understanding and exploring problem-based strategy models to improve students' critical thinking skills in social studies learning. Critical thinking skills in students are needed in this global era, namely to improve competitive abilities, overcome everyday problems, and prepare emotional maturity. student. with the hope that students can be more independent, can develop thinking skills, can develop inquiry and are also more critical of solving problems in their social environment. This study uses a qualitative method with the type of literature study, where the results and discussion obtained are the results of previously existing summaries. In this case, what must be considered when designing the concept of learning is how to determine the right learning strategy model. Problem-based learning strategy (SPBM) is a strategy model that has been widely used by teachers throughout Indonesia. This strategy model applies the discovery method, so that students are expected to be better able to recognize and describe their full learning capacity and potential, realize and be able to use the potential of learning resources around them. In this paper, we will discuss a little problem-based strategies to improve students' critical thinking skills in social studies learning, which includes several aspects, first, there is the nature of social studies learning. second, problem-based learning strategies. Third, the steps in problem-based social studies learning, fourth, critical thinking skills.